Süleyman Senih ve Müşterek Gazelleri - Alıcı, Lütfi (Kitabevi, 2003)
Classical Turkish literature is mainly poetry dominant literature. Among the poetry style gazel is primarily important. Among the gazel style which developed many variations in time common gazels which were composed by two or three poets attract the attention. The first examples of common gazels given by Nabi and Abdi were respected by the 19th century poets. In this century one of the poets which composed common gazels most is Süleyman Senih. Common gazels reflect literary circles in which they are composed, the interactions and connections among poets and many other essential issues. From this point of view, common gazels are vital literary texts for the history of Turkish literature.
Süleyman Senih and His Common Gazels
Keywords: Süleyman Senih; Common Gazel; Folk Literature; Repartee